2023
DOI: 10.3390/healthcare11050714
|View full text |Cite
|
Sign up to set email alerts
|

Initial Development of a Patient-Reported Experience Measure for Older Adults Attending the Emergency Department: Part II—Focus Groups with Professional Caregivers

Abstract: A wide range of healthcare professionals provide care for patients in the emergency department (ED). This study forms part of a wider exploration of the determinants of patient experience for older adults in the ED, to assist the development of a new patient-reported experience measure (PREM). Inter-professional focus groups aimed to build on findings from earlier interviews with patients conducted in the ED, by exploring professional perspectives on caring for older people in this setting. A total of thirty-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…An initial list of candidate items was developed by two researchers (B. G. and J. M. L.) following methodological triangulation of findings from prior studies conducted by the research team. These consisted of a qualitative metasynthesis of 22 studies of patient experience in the ED 17 ; interviews conducted with 24 patients aged over 65 attending the ED 18 ; and interprofessional focus groups with 37 ED staff 19 . Methodological triangulation describes the use of multiple data sources to study a phenomenon, and is useful to confirm findings, enrich data and increase overall validity 20 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…An initial list of candidate items was developed by two researchers (B. G. and J. M. L.) following methodological triangulation of findings from prior studies conducted by the research team. These consisted of a qualitative metasynthesis of 22 studies of patient experience in the ED 17 ; interviews conducted with 24 patients aged over 65 attending the ED 18 ; and interprofessional focus groups with 37 ED staff 19 . Methodological triangulation describes the use of multiple data sources to study a phenomenon, and is useful to confirm findings, enrich data and increase overall validity 20 .…”
Section: Methodsmentioning
confidence: 99%
“…These consisted of a qualitative metasynthesis of 22 studies of patient experience in the ED 17 ; interviews conducted with 24 patients aged over 65 attending the ED 18 ; and interprofessional focus groups with 37 ED staff. 19 Methodological triangulation describes the use of multiple data sources to study a phenomenon, and is useful to confirm findings, enrich data and increase overall validity. 20 Therefore, similar findings that occurred across more than one of the studies were identified as particularly relevant as a focus for future measurement of older adults' experiences of ED care.…”
Section: Item Generationmentioning
confidence: 99%
See 2 more Smart Citations